Anesthesiological perspective on the obese patients: challenges and management - literature review - Telega, Stanisław; Bollin, Paweł; Szymczak, Urszula; Lachór, Wojciech Wiesław; Solarz, Monika Barbara; Piekarska, Julia; Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika; Robak, Jakub (Quality in Sport, 2025)
Obesity has become a widespread health problem with important implications for various medical disciplines. Obese patients, particularly those who are extremely obese, present unique challenges to anaesthetic management, requiring specialized approaches to adapt management to their altered anatomy, physiology, and increased risk of complications. These patients are more likely to experience difficulties with the airway, ventilation, and drug pharmacokinetics, complicating standard anaesthetic techniques. The impact of obesity on respiratory mechanics poses additional risks during surgery and in the perioperative period. In addition, the multiple comorbidities associated with obesity further increase the complexity of anaesthetic management. This review aims to outline current anaesthetic approaches to the management of obese patients, with a focus on airway management, ventilation techniques, and use of medications. It also discusses innovative methods such as ultrasound prediction of the risk of difficult airways and strategies to optimize oxygenation during surgery. This article brings together the latest evidence on how these techniques improve patient outcomes, reduce the risk of complications, and enhance the safety of anaesthesia. This review provides valuable insights for anesthesiologists and healthcare providers to improve care for obese patients undergoing surgery.